2018
DOI: 10.1002/erv.2598
|View full text |Cite
|
Sign up to set email alerts
|

Are treatment results for eating disorders affected by ADHD symptoms? A one‐year follow‐up of adult females

Abstract: A high degree of ADHD symptoms may have a negative impact on recovery in ED. Screening/diagnostic evaluation of ADHD in all loss of control over eating/bingeing/purging ED patients and studies of the effect of implementing ADHD-treatment strategies in this patient group are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…The only previous study investigating the effect of ADHD over treatment for ED suggested that patients with higher ADHD symptoms presented a higher risk of poor post-treatment outcome, although the impact of ED severity on this relation was not assessed [ 26 ]. Interestingly, a high dropout from treatment was also reported in that study (61%), further suggesting the importance of taking into account dropout as a negative outcome of ED treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only previous study investigating the effect of ADHD over treatment for ED suggested that patients with higher ADHD symptoms presented a higher risk of poor post-treatment outcome, although the impact of ED severity on this relation was not assessed [ 26 ]. Interestingly, a high dropout from treatment was also reported in that study (61%), further suggesting the importance of taking into account dropout as a negative outcome of ED treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the evidence linking ADHD and EDs, there is a lack of studies investigating whether ADHD symptoms may impact treatment response in patients with EDs, both in terms of treatment adherence (i.e., dropout rate) and outcome. To the best of our knowledge, there is only one previous study in female patients with EDs reporting higher ADHD symptoms at baseline as a predictor of non-recovery from eating-related symptomatology one year after treatment, especially for patients with loss of control overeating, bingeing and purging [ 26 ]. However, a high dropout rate (61%) was shown in that study, highlighting the need for future studies examining the impact of ADHD symptoms over dropout rate in EDs treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Hypothesis testing studies analyze the empirical evidence obtained in a specific sample with different purposes: (a) to identify risk factors and underlying mechanisms that enable a better understanding of the etiology and the phenotypes of disorders [e.g. the study by Mallorquí‐Bagué and colleagues aiming at investigating clinical and electrophysiological correlates of emotion regulation and craving regulation in anorexia nervosa (AN) (Mallorquí‐Bagué et al, 2020)]; (b) to assess the therapeutic efficacy of treatments [such as the study by Fernández‐Aranda and colleagues analyzing the benefits of a serious video game (SVG) as a complementary program to enhance the general functioning of patients with BN (Fernandez‐Aranda et al, 2015)]; and (c) to find out the evolution over time of different disorders and their possible correlated factors [such as the work by Svedlund and colleagues, which assessed whether the efficiency of a medium‐term intervention in women with ED may be due to attention deficit hyperactivity disorder symptoms (Svedlund, Norring, Ginsberg, & von Hausswolff‐Juhlin, 2018), or the randomized clinical trial (RCT) by Loeb et al aimed at assessing the efficacy of family‐based treatment for paediatric obesity (FBT‐PO), when compared with nutrition education counselling for weight management (Loeb et al, 2019), or the study by Giombini and colleagues analyzing the benefits of using individual cognitive remediation therapy in inpatient setting with Anorexia nervosa (Giombini et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Chronologically, ADHD most often emerges earlier in life than ED, and girls with ADHD have an increased risk of later developing BN (Biederman et al, 2010). Additionally, a high degree of ADHD symptoms, at the time when ED treatment is initiated, has been identified as a negative prognostic factor for recovery at 1 year follow‐up (Svedlund, Norring, Ginsberg, & von Hausswolff‐Juhlin, 2018). This emphasizes the clinical significance of an interaction between ED and ADHD.…”
Section: Introduction and Aimsmentioning
confidence: 99%